Tonga : 2020 Article IV Consultation and Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Tonga. (IMF Staff Country Reports; Country Report ;, 2021)
Tonga's recovery following the devastation of the 2018 Cyclone Gita has been derailed by a double blow from the pandemic and Cyclone Harold. FY2020 GDP growth is estimated to fall to -2 1\2 percent due to domestic containment measures, a sudden stop in tourism, and investment delays. The full brunt of the pandemic will be felt in FY2021 (beginning July) during peak tourism season, when a deeper contraction is expected. A worse outcome was avoided by early actions to close external borders-which has kept Tonga COVID-19-free-and prompt economic support. Beyond FY2021, the recovery is expected to resume in line with the global recovery, but the magnitude and trajectory is uncertain.